2015
DOI: 10.1002/suco.201400070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the location of broken wire wraps on the failure pressure of prestressed concrete cylinder pipes

Abstract: 1 Introduction and backgroundPrestressed concrete cylinder pipe (PCCP) has been used for large-diameter water transmission and distribution mains in the United States as lined cylinder pipe (LCP) since 1942 and as embedded cylinder pipe (ECP) from 1952 onwards. Many classes of ECP have been standardized by the industry based on their internal fluid pressure capacity and backfill earth pressure capacity. The concrete core and prestressing wire are the main structural components, while the steel cylinder acts pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Additionally, it is not practical to fully model the actual condition of each damaged joint. To simplify the modeling details and reduce computational costs, in previous studies the joints were assumed to conservatively have no interaction or full interaction between the bell end and spigot end (Alavinasab et al, 2013;Alavinasab and Hajali, 2014;Hajali et al, 2015). In this paper, the interactions between the PCCPs were defined by normal behavior (hard contact) and tangential behavior (contact algorithm).…”
Section: Pccp Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is not practical to fully model the actual condition of each damaged joint. To simplify the modeling details and reduce computational costs, in previous studies the joints were assumed to conservatively have no interaction or full interaction between the bell end and spigot end (Alavinasab et al, 2013;Alavinasab and Hajali, 2014;Hajali et al, 2015). In this paper, the interactions between the PCCPs were defined by normal behavior (hard contact) and tangential behavior (contact algorithm).…”
Section: Pccp Jointmentioning
confidence: 99%
“…As the number of broken wires increases, the bearing capacity of the PCCP sharply decreases, and the risk of pipe burst increases. Moreover, the wire break damage of the bell-and-spigot joint can decrease the overall strength of the PCCP more than that in the barrel of the pipe (Alavinasab et al, 2013;Hajali et al, 2015Hajali et al, , 2016b. Few studies available in the literature have thoroughly investigated the possible coupling disaster of PCCP pipelines in service.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al 7 analyzed the key factors affecting the rotation angle of PCCP on soft soil foundation based on field tests and numerical calculations, and proposed some measures to control the rotation angle of joint. Hajali et al [8][9][10] studied the effect of wire broken position and number on the ultimate internal pressure of PCCP through a three-dimensional (3D) nonlinear finite element model, and the interaction between bell and spigot was considered, the results of which showed that the occurrence of wire broken at joint can influence the performance of PCCP mostly. Hu et al 11 analyzed the relationship between settlement and rotation angle at joints through laboratory tests, and studied the strain distribution at joints.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that broken wires do not have a significant impact on a PCCP with good mortar adhesion. Hajali et al [24][25][26] considered the pipe-soil interaction, the interaction between neighboring pipes, and internal and external loads in modeling the effects of the position and number of broken wires on a PCCP using a three-dimensional finite element model.…”
Section: Introductionmentioning
confidence: 99%